A collection of aspect ratios of common clay minerals determined from conductometric titrations. (June 2014) - Weber, C.; Heuser, M.; Stanjek, H.
Abstract: The aspect ratios of common clay minerals have been determined from conductometric titrations. The sample set comprises 11 Na-saturated bentonites, 16 smectites with different interlayer cations, three illites/muscovites and two talc dominated specimens. It is shown that the aspect ratios of smectites saturated with divalent cations are lower than those of the same smectite saturated with a monovalent cation. This observation is discussed in terms of the number of smectite layers making up a particle.